Chinese secondary school teachers’ conceptions of L2 assessment: A mixed-methods study - Ma, Maggie; Bui, Gavin (Studies in Second Language Learning and Teaching, 2021)
Teacher conceptions of assessment influence their implementation of learning-focused assessment initiatives as advocated in many educational policy documents. This mixed-methods study investigated Chinese secondary school teachers’ conceptions of L2 assessment in the context of an exam-oriented educational system which emphasizes English grammar, vocabulary and reading comprehension skills. For the quantitative part of the study, survey data were collected to gauge the conceptions of assessment held by 66 senior secondary EFL teachers from six schools in Eastern China. For the qualitative part, case studies of two teachers from schools with different rankings were conducted. Quantitative results showed that the teacher participants as a group agreed most with the view that assessment is to help learning. However, there was a strong association between two factors, that is, the assessment as accurate for examination and teacher/school control factor, and the assessment as accurate for student development factor. The strong association indicated that it may be less likely for the group of teachers to adopt the formative assessment initiatives emphasizing student development as promoted in the English curriculum reform. Qualitative findings further revealed individual differences in the two case study teachers’ conceptions and practices of assessment as well as the interplay among meso-level (e.g., school factor), micro-level (e.g., student factor), and macro-level (e.g., sociocultural and policy contexts) factors in shaping the teachers’ different conceptions and practices of assessment. A situated approach has been proposed to enhance teachers’ assessment literacy.